Challenges of caring for the aged: Attracting and retaining aged care assistants in Western Australia. (27th August 2020) - Dhakal, Subas P.; Nankervis, Alan; Connell, Julia; Burgess, John
Abstract: Objectives: To report on the attraction and retention challenges concerning Aged Care Assistants (ACAs) in the state of Western Australia (WA) and to identify the related specific 'push‐and‐pull' factors. Methods: A self‐administered survey resulted in a 20.2% response rate (79/391) from nine WA residential aged care facilities. The key purpose of the survey was to explore the reasons why ACAs might remain in their jobs or leave for other occupations. The χ 2 test was employed to determine statistically significant associationsbetween intention to stay in the job and each of the independent variables . Results: Those who were younger, casually employed and working in urban areas were more likely than their counterparts to state their intention to leave their workplace in the next year. Conclusion: In line with the national emphasis on the attraction and retention of ACAs, the findings reported here have the potential to inform future strategies in residential aged care facilities in WA.